2004
DOI: 10.1128/aem.70.6.3392-3400.2004
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Content Governs Fermentation Rate in Nitrogen-Deficient Wine Musts

Abstract: Problematic fermentations are common in the wine industry. Assimilable nitrogen deficiency is the most prevalent cause of sluggish fermentations and can reduce fermentation rates significantly. A lack of nitrogen diminishes a yeast's metabolic activity, as well as the biomass yield, although it has not been clear which of these two interdependent factors is more significant in sluggish fermentations. Under winemaking conditions with different initial nitrogen concentrations, metabolic flux analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
181
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(204 citation statements)
references
References 42 publications
19
181
2
2
Order By: Relevance
“…However, the amount of DNA was not affected, being constant at the level of 0.5% of the cell dry weight. It was reported that macromolecular compositions of S. cerevisiae were liable to change with the variation of heterologous gene expression (Gonzalez et al, 2003) and environmental conditions such as dilution rate and nitrogen deficiency (Nissen et al, 1997;Varela et al, 2004). Macromolecular compositions such as protein and RNA serve as the basis of metabolic behaviors.…”
Section: Impact On the Biosynthesis Of Intracellular Compositionsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the amount of DNA was not affected, being constant at the level of 0.5% of the cell dry weight. It was reported that macromolecular compositions of S. cerevisiae were liable to change with the variation of heterologous gene expression (Gonzalez et al, 2003) and environmental conditions such as dilution rate and nitrogen deficiency (Nissen et al, 1997;Varela et al, 2004). Macromolecular compositions such as protein and RNA serve as the basis of metabolic behaviors.…”
Section: Impact On the Biosynthesis Of Intracellular Compositionsmentioning
confidence: 99%
“…The metabolic flux analysis of the self-flocculating yeast was performed using the stoichiometric models from Nissen et al (1997) and Varela et al (2004) with modifications that incorporated 10 transport reactions across the membranes, trehalose, and ergosterol synthesis reactions as listed in Appendix.…”
Section: Stoichiometric Model For Metabolic Flux Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of nitrogen required for biomass synthesis can be estimated from the empirical formula for a bacterial cell as C 5 H 7 O 2 N [47]. Previous studies on the effect of nitrogen on ethanol fer-mentation have shown the adverse effects of nitrogen deficiency [48] [49] [50]. The lack of nitrogen diminishes yeast's metabolic activity, sugar uptake rate, and the cell biomass during fermentation.…”
Section: Protein Recoverymentioning
confidence: 99%